Status of Cardiac Surgical Intensive Care Medicine in Germany in 2018: A Report on Behalf of the German Society for Thoracic and Cardiovascular Surgery - Markewitz, Andreas; Lewandowski, Jana; Trummer, Georg; Beckmann, Andreas (The Thoracic and Cardiovascular Surgeon, 2020)
Background This report summarizes the results of a voluntary survey designed to assess the current situation of cardiac surgical intensive care medicine in Germany in 2018.Methods A standardized questionnaire concerning detailed information about structural characteristics of cardiac surgical intensive care units (ICUs) was sent to all German departments performing cardiac surgery.Results Response rate was 93% (n = 75/81). Compared with previous surveys since 1998, the median number of intensive care beds for patients after cardiac surgery increased from 15 in 2013 to 16 in 2018. The proportion of cardiac surgical ICUs decreased to 51% with a simultaneous increase of interdisciplinary ICUs. The proportion of cardiac surgeons acting as director of an ICU increased to 43%. The physicians' teams were mostly interdisciplinary (57%). More than half of the directors were board-certified intensivists (62%) with a peak of 100% in ICUs run by cardiac surgeons. Human resources development in the ICU showed similar trends with an increase of physicians and nurses. More than half of all ICUs (61%) and the vast majority of cardiac surgical ICUs (82%) offer an accredited training program for intensive care medicine.Conclusion The results of this survey corroborate once again that intensive care medicine represents a substantial and important part of cardiac surgery. However, efforts are necessary to keep this attitude alive for the future.
Keywords: cardiac surgery; intensive care medicine; survey; data; quality